Contingency Management in an Athletic Study Hall - Glenn, Sigrid S.; Bruce, Gary; Ellis, Janet; Rollins, Linda (My University, 1986)
A contingency management system, cooperatively developed in NTSU's School of Community Service and the Athletic Department was implemented to increase the amount of time student athletes (with GPAs below 2.0) spent studying. Repeated reversals were used to demonstrate effectiveness of the contingencies used-i.e., students' on-task study behavior (looking at books, underlining or making notes, memorizing with book open) resulted in early release from study hall. Data takers observed individual students every 7 seconds and those meeting a 90% on-task criterion left study hall 30 minutes early. Data are included that demonstrate the effectiveness of this early-release contingency on proportion of time spent studying. Increasing numbers of students were released on-task ov er time. Additionally, data were collected on numbers choosing to remain in study hall after given permission to leave.
Keywords: study hall